Trauma and Compassionate Blame - Alycia W. LaGuardia-LoBianco (Ergo, An Open Access Journal of Philosophy)
A common question in moral philosophy concerns how we should regard traumatic histories that have influenced wrongdoing. In this paper, I argue that one standard line of response—survivors are exempt from blame for a given wrongdoing because of a traumatic history that influenced this wrongdoing—is problematic. Instead of trying to determine how trauma categorically exempts survivors from blame, I argue that we should start from the fact that survivors are members of the moral community who can be as blameworthy as anyone, and then ask how considerations of trauma might impact a moral response to their wrongdoing. I consider and reject three attempts to exempt survivors on the grounds of traumatic histories, arguing that each risks divesting survivors of moral agency. I then develop an account of compassionate blame, a unique attitude in which we can blame the survivor for their wrong while also taking compassion towards the survivor in light of their traumatic history, and argue that this is the appropriate moral attitude to cultivate in these cases.